Dynamics of Cultural Commodification in Tourism Development in the Karo Region and Its Implications for Sustainability - Nasution, Rahmad Kurnia Abdik; Sitti Nurlaeli (Brilliant International Journal Of Management And Tourism, 2025)
This study explores the dynamics of cultural commodification in the tourism development of the Karo region in North Sumatra, Indonesia, an area rich in traditional architecture, rituals, oral arts, and symbolic textiles. Despite its cultural vibrancy, the region faces increasing pressures from tourism growth and digital media exposure, which have led to the transformation of cultural expressions for commercial consumption. The research focuses on how these commodification processes reshape cultural meanings, alter community agency, and challenge the sustainability of Karo cultural identity. The study aims to classify the forms of cultural commodification in Karo tourism and assess their implications for cultural preservation. Using a qualitative methodology, the research integrates a systematic review of literature, analysis of tourism-related documents, and examination of digital cultural representations on platforms like YouTube, TikTok, and Instagram. The analysis identifies three forms of commodification: (1) performative commodification, where cultural ceremonies and performances are adapted for tourists; (2) visual commodification, where Karo culture is aestheticized in digital media; and (3) material commodification, seen in the commercialization of cultural symbols like Uis Gara motifs. While these practices create economic opportunities, they also risk diminishing cultural depth and authenticity. The study concludes that enhanced cultural governance, community participation, and responsible creative economy development are crucial for long-term cultural sustainability.